2010
DOI: 10.1262/jrd.1056s22
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dry and Transition Cows to Improve Energy Balance and Reproduction

Abstract: Abstract. Fertility of dairy cows has decreased for the past several decades. Measures of energy balance (EB; e.g. change in EB, EB nadir, cumulative negative EB, or duration of negative EB) are related to reproductive performance. Our research group has concluded that modification of diets fed during the dry or transition period are unlikely to have significant effects on postpartum EB and fertility. Rather, more radical alterations in dairy management are needed if energy status of postpartum cows is to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 20 publications
1
30
0
4
Order By: Relevance
“…This transition is the most stressful period of the cow's life and has a large impact on a cow's lactation production. As a result, , 80% of dairy -E-mail: kplaut@purdue.edu cow disease events occur in the first 3 weeks after a cow delivers a calf (Drackley, 1999;Mulligan and Doherty, 2008;Grummer et al, 2010;LeBlanc, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transition is the most stressful period of the cow's life and has a large impact on a cow's lactation production. As a result, , 80% of dairy -E-mail: kplaut@purdue.edu cow disease events occur in the first 3 weeks after a cow delivers a calf (Drackley, 1999;Mulligan and Doherty, 2008;Grummer et al, 2010;LeBlanc, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This transition is the most stressful period of the cow's life and has a large impact on a cow's lactation production. As a result, , 80% of dairy -E-mail: kplaut@purdue.edu 394 cow disease events occur in the first 3 weeks after a cow delivers a calf (Drackley, 1999;Mulligan and Doherty, 2008;Grummer et al, 2010;LeBlanc, 2010).Understanding how a cow sets her metabolic and physiological rhythms in response to changes in her physiology, nutritional status and/or environment will enable the development of simple approaches that maximize productive efficiency and minimize metabolic disturbances in dairy cows. The circadian system is a likely candidate as it is believed to have evolved to coordinate the timing of internal physiological and metabolic processes and synchronize this timing with the animal's environment.…”
mentioning
confidence: 99%
“…Studies have shown improvement in reproductive performance with a shorter dry period in multiparous animals. Due to shorter dry periods, the postpartum negative energy balance is improved, resulting in fewer days to first ovulation and a greater success of artificial insemination (Watters et al, 2009;Grummer et al, 2010;Mansfeld et al, 2012). This may have an impact on the overall calving interval, which showed a decreasing trend in the vaccinated herds over the years, whereas an adverse trend was observed in nonvaccinated herds (Fig.…”
Section: Reproduction and Milk Productionmentioning
confidence: 99%
“…Our results showed that feeding cows with an additional energy source succeeded to avoid severe postpartum blood IGF-I and thyroid hormone depression. Namely, after parturition high yielding dairy cows are exposed to NEB (Grummer et al, 2010). Thyroid hormones are positively correlated with energy balance in dairy cows during the early lactation period (Stoji} et al, 2001), and their concentrations decrease after calving.…”
Section: Igfbp-4mentioning
confidence: 99%